A trigonal prismatic Cu6-pyrazolato complex containing a μ6-F ligand - Mathivathanan, L; Al-Ameed, K; Lazarou, K; Trávníček, Z; Sanakis, Y; Herchel, R; McGrady, JE; Raptis, RG (Royal Society of Chemistry, 2015)
The encapsulation of a fluoride ion in a trigonal prismatic CuII6-pyrazolato cage results in a small expansion of the Cu6-host. The structural, electronic and magnetic features of the Cu6-complex, containing an endohedral fluoride in the rare μ6-F coordination mode, are compared with those of the parent complex with a vacant Cu6-cage.